Blending Myth and Reality: Minamoto no Yoshitsune in the Realm of Video Games (Genji: Dawn of the Samurai) - Saputra, Ekky Irwan; Ayyub, Ichlasul (Vocational College of Diponegoro University, 2025)
This study explores the life and legacy of Minamoto no Yoshitsune, an important historical figure from Japan's Genpei War, along with his portrayal in console games: Genji: Dawn of the Samurai. This study employs qualitative historical methods and semiotic analysis grounded in Roland Barthes' theories to explore the reinterpretation of Yoshitsune's historical and mythological narratives within video games. The examination emphasizes visual and narrative components to reveal both denotative and connotative meanings, delving into the convergence of historical accuracy and artistic interpretation. The findings indicate that although game incorporates distinct creative elements, including supernatural powers and improved visual aesthetics, they maintain the core essence of Yoshitsune as both a heroic and tragic character. His portrayals consistently highlight themes of bravery, endurance, and selflessness, reflecting his iconic status in Japanese culture. The analysis emphasizes the significance of video games in enhancing the cultural memory of historical figures through the integration of factual narratives and imaginative storytelling. These reinterpretations captivate contemporary audiences and highlight the dynamic evolution of historical narratives within interactive media. Future studies could delve deeper into the cultural significance of gaming as a means of preserving and reinterpreting historical identities.